Review of Dimitris Papanikolaou, Greek Weird Wave: A Cinema of Biopolitics - Kravva, Valia (Historein, 2024)
Review of Dimitris Papanikolaou, Greek Weird Wave: A Cinema of Biopolitics. Edinburgh: Edinburgh University Press, 2021. 224 pp.